Deep Low‐Frequency Earthquakes Associated With the Eruptions of Shinmoe‐dake in KirishimaVolcanoes. Issue 12 (17th December 2019) - Kurihara, Ryo; Obara, Kazushige; Takeo, Akiko; Tanaka, Yusaku
Abstract: Deep low‐frequency (DLF) earthquakes occur beneath the Kirishima volcanoes in southwest Japan at depths of 10–30 km. In this study, we aim to reveal the relationship between DLF earthquakes and volcanic activity including eruptions by relocating the hypocenters of the earthquakes using the network correlation coefficient method and detecting the earthquakes comprehensively using the matched filter technique. Hypocenters of DLF earthquakes are found to be concentrated in some separated small clusters within depths of 10–15 and 20–27 km. Activation of deeper DLF earthquakes had been observed for approximately 2 years from December 2009, during which various styles of eruptions occurred. Such a 2‐year increase in DLF seismicity was well correlated with crustal deformation because of the volume change of a magma reservoir. The waveforms and hypocenters of DLF earthquakes during the activation period were different from those during other time periods. The activated DLF earthquakes mostly had low dominant frequencies and were located in four deeper clusters. The activation of each cluster was switched 3 times at the transition of the eruption styles. These results suggest that DLF earthquakes might occur near magma sills and could be triggered by fluid flow in the changing paths by complex eruption processes. In addition, the waveforms and hypocenters of DLF earthquakes associated with the 2018 eruptions are different from those associated with the 2011 eruptions. The fluid paths of the 2018 eruptions might be different from those of the 2011 eruptions. Plain Language Summary: Deep low‐frequency (DLF) earthquakes occur at depths of 10–30 km beneath the Kirishima volcanoes, which is one of the most active volcanoes in Japan. In the last decade, two major series of eruptions were observed there. The relationship between DLF earthquakes and volcanic activity such as eruptions is still unknown; therefore, we conduct two analyses, namely, relocation and detection to obtain the precise spatial distribution and comprehensive temporal distribution of DLF earthquakes based on waveform correlations. The result is that DLF earthquakes occurred in some small clusters, having been activated for approximately 2 years from December 2009, during which various styles of eruptions including subplinian eruptions on 26–27 January 2011 occurred. The long‐term increase in DLF earthquakes was well correlated with crustal deformation because of the volume change of the magma reservoir. Most DLF earthquakes associated with the 2011 eruptions are distributed in four deeper clusters that are different from those of DLF earthquakes in the other time periods. Moreover, the clusters were switched 3 times, which approximately correlates with the transitions of eruption styles. These results suggest that DLF earthquakes were triggered by fluid flow in the deep crust related to the eruptions. Key Points: Activation of low‐frequency earthquakes at depths of 20–27 km started 1 year before the 2011 eruptions of Shinmoe‐dake Waveforms of low‐frequency earthquakes associated with the 2011 eruptions indicate lower dominant frequencies than those of the others Activated low‐frequency earthquake locations might have been switched by fluid path redistribution with eruption style transitions